Challenges for Leadership in a Private University in a Context of Poverty: Impact of Lack of Access to Higher Education in Tekax, Yucatan, Mexico - Ortiz-Navarro, Juan Carlos (2019)
The present research work, in the first instance, defines the construct poverty and vulnerability, the reasons why poverty and vulnerability were nested in Latin America and of course in Mexico. In the same way, the investigation evidences the levels of poverty existing in Mexico at present, as well as, its causes particularly in the State of Yucatan, to later make a revision and analysis on different cases of success in the fight against poverty, economic and social development through human, intellectual and social capital development strategies, in countries whosesocioeconomic characteristics are similar to living conditions in Mexico and the State of Yucatan, in order to understand why these other economies (mainly the Eastern of Asia) have achieved great progress in terms of economic and social development, while Mexico, despite its great economic capacity, has not been able to achieve the same results in terms of poverty and vulnerability reduction, economic and social development refer. To conclude and recommend complementary guidelines that the Yucatecan society could implement, to improve the welfare levels of population in Tekax.